Regional Economic Outlook, April 2008, Western Hemisphere. (Regional Economic Outlook; April 2008, 2008)
The main focus of this report is the outlook for the region in the face of the downturn now projected for the U.S. economy and the continuing risks that affect the global outlook. Overall the region is better placed than in the past to navigate the current financial turbulence, given reduced vulnerabilities and stronger policy frameworks. Nonetheless, the report points to risks that the global financial stress could curtail capital flows to the region and world commodity prices could fall more than expected. There are also risks arising from rising inflation and rapid private credit growth in a number of countries. The report then explores the policy options facing governments in the region, underscoring the need to preserve the gains of recent years.